Manajemen Fundraising Wakaf Produktif: Perbandingan Wakaf Selangor (PWS) Malaysia dan Badan Wakaf Indonesia - Jauhar Faradis; M. Yazid Affandi; Slamet Khilmi (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2015)
This research is motivated by the low public understanding of the productive waqf and magnitude of potential productive waqf. The purpose of this resesarch is to analyze the condition of BWI and PWS. Results showed that the strategy is the collection of productive waqfperformed by BWI and PWS there are two methods namely: the first method of "waiting for the ball." The second method "pick up the ball. Method" waiting for the ball ", this method starts with opening an account at Financial Institution Shariah waqf Receiver on behalf of BWI. While PWS started by opening kaunter PWS, open an account at Financial Institution Shariah waqf Receiver top name PWS, Skim Infaq (salary), Ejen, and portal e-Mais. And in cooperation with educational institutions. Method " pick up the ball " means that the direct interaction between BWI with prospective wakif by approaching directly to the agency-intansi both public and private. Where as PWS using three models: first, female Moon and waqf, Second, Month selangor waqf, and the third month Masre Industry.